2012
DOI: 10.1016/j.jcrs.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Technique to exclude temporal lash incursion in phacoemulsification surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…1 Eye trauma, often occurring through physical activity, is the leading cause of noncongenital monocular blindness in children. 2,3 Blunt trauma accounts for most sportsrelated eye injuries and, depending on the mechanism of injury, can cause many presentations, including hyphema.…”
Section: Traumatic Hyphema In Badminton Players: Should Eye Protectiomentioning
confidence: 99%
See 2 more Smart Citations
“…1 Eye trauma, often occurring through physical activity, is the leading cause of noncongenital monocular blindness in children. 2,3 Blunt trauma accounts for most sportsrelated eye injuries and, depending on the mechanism of injury, can cause many presentations, including hyphema.…”
Section: Traumatic Hyphema In Badminton Players: Should Eye Protectiomentioning
confidence: 99%
“…Hyphema can lead to permanent vision loss through secondary glaucoma, optic atrophy, and corneal bloodstaining. 2,3,4 Based on statistics collected from 1972 to 2002, the Canadian Ophthalmology Society reports that the most common sports that cause ocular injury in Canada are hockey, racquet sports, and baseball. 5 Badminton accounts for the most reported eye injuries compared to all racquet sports combined in Canada.…”
Section: Traumatic Hyphema In Badminton Players: Should Eye Protectiomentioning
confidence: 99%
See 1 more Smart Citation
“…Eyelashes, as a source of fibres, were probably not a cause for concern in this study, as the surgeon had previously implemented a strict exclusion technique involving the use of Steri-Strip's (3 M, St Paul, MN, US). 17 As demonstrated, when a capable surgical assistant is present, a large proportion of the fibres may be effectively removed from the surgical field. The elimination of fibres, as they are seen, must remain the principle form of retained fibre prevention.…”
Section: Fibres Found In the Eye During And After Pcs Ze Mcpherson Et Almentioning
confidence: 99%
“…Furthermore, patients with long, rigid eyelashes may respond well to definitive temporal lash exclusion. 3 Rudnisky et al reported that cataract surgery performed at a low-volume, private surgery center was associated with a higher rate of PCSE. This may have occurred because the low-volume surgeon was dealing with patients with denser nuclei, a later presentation, underlying systemic infections or illnesses including impaired immunity, or advanced age.…”
mentioning
confidence: 99%